Productivity and quality of grain pea varieties cultivated in the Azov area of the Rostov region depending on hydrothermal factors - A. A. Lysenko (Зерновое хозяйство России)
The current paper has presented the three-year study results of the impact of the regime of the main agrometeorological indicators (the amount of precipitation during the vegetation period, temperature and hydrothermal coefficient) on the size and quality of the yield of grain pea varieties of domestic and foreign breeding. It is most effective to cultivate high-yielding technological pea varieties with good grain quality, well adapted to various growing conditions (drought, waterlogging). On average, over the three years of study, productivity increase of the varieties ‘Sotnik’, ‘Amulet’, ‘Premier’, ‘Aliyans’, ‘Kadet’, ‘Ataman’,’ KVS La Mansh’ and ‘Glyans’ was on 0.57 t/ha more than that of the standard variety ‘Aksai Usatiy 5’. There have been identified the varieties ‘Kadet’, ‘Premier’, ‘Amulet’, ‘Velvet’ and ‘KVS La Mansh’ with a high protein percentage in grain (27.3–28.0%). According to the obtained results, we can say that protein percentage in grain of the studied pea varieties is directly affected by both the hydrothermal coefficient during the vegetation period and the productivity. The purpose of the current study was to investigate and analyze productivity and seed quality of the pea varieties, depending on the hydrothermal conditions in the Azov agro-climatic area of the Rostov region. These results obtained can be used in further breeding work. It is important that these varieties are adaptive to the soil and climatic conditions of the Rostov region, they are the initial material for breeding new highly productive pea varieties with a complex of economically valuable traits, as well as for growing under production conditions.